Variants of the FTO Gene in Obese Children and their Impact on Body Composition and Metabolism before and after Lifestyle Intervention - Schum, J.; Blumenstock, G.; Weber, K.; Schweizer, R.; Pfaff, C.; Schurr, N.; Ranke, M. B.; Binder, G.; Ehehalt, S.; null (Experimental and Clinical Endocrinology & Diabetes, 2012)
To investigate the impact of variants of the FTO gene (rs1421085, rs17817449, rs9939609) in obese children before and after lifestyle intervention.Design: Longitudinal, clinical intervention study with an increase in physical activity, and nutritional recommendations based on the Optimized Mixed Diet for German Children and Adolescents’ (Research Institute of Child Nutrition, Germany). Study population: 75 overweight children (40 male, mean BMI 30.4±5.5 kg/m2, mean age 12.6±2.6 years). Measurements: Genotyping by means of a TaqMan SNP genotyping assay. Lean and fat mass were determined by means of DXA.For the whole study population, the 6-month lifestyle intervention resulted in a significant improvement (before intervention minus time point 6 months; mean±SD) in BMI-SDS (0.10±0.17, p<0.001), HOMA (1.41±3.19, p<0.001) and relative fat-mass-SDS (0.09±0.23, p=0.005). Before and after lifestyle intervention, there was no significant difference between heterozygote (n=52) and homozygote (n=21) carriers of the FTO gene in terms of BMI, body composition, and the metabolic profile (Insulin, HOMA, lipids, liver function tests).Variants in the FTO gene are common in obese children but have no impact on body composition and metabolism before and after lifestyle intervention.
Keywords: FTO gene; body composition; metabolism; children